RESPONSE OF WHITE MUSTARD (SINAPIS ALBA L) TO SPACING UNDER RAINFED CONDITIONS - F. U. Hassan; M. Arif (Journal of Animal and Plant Sciences, 2012)
Growth and development of individual plants is modified with space available to plants. However, many crop species having tillering or branching mechanisms allow similar levels of yield and dry matter production per unit area from a range of planting densities. Response of white mustard (Sinapis alba L) to spacing was studied through field experiment conducted at PMAS-Arid Agriculture University, Research Farm, Chakwal Road, Rawalpindi during Rabi 2008-09. Nine plant to plant spacings (5, 7.5, 10, 12.5, 15, 17.5, 20, 22.5 and 25 cm) were laid out in randomized complete block design, when rows were 20 cm spaced. The experiment had three replications in net plot size of 2 x 6m. Plant spacing significantly affected all plant characteristics: plant height, branches, pods per plant, seeds per pod, thousand seed weight and seed yield. Although, no consistent pattern of increase or decrease of any parameter was exhibited by plants due to spacing, however, plant height showed linear relationship with spacing while inverse relationship was observed for seed yield. Plants spaced at 15 cm depicted the highest values for seed yield and related parameters. Thus, it may be concluded that white mustard (Sinapis alba L) should be grown at 15 cm spacing when rows are 20 cm spaced with projected plant population of over three hundred thousand per hectare to have profitable yield.
Keywords: White mustard; plant spacing; row spacing; compensatory mechanism.